PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, DAN PROGRAM SAMSAT CORNER TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Dewi Kusuma Wardani; Moh. Rifqi Asis (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aimed to examine the effect of knowledge of the taxpayer, the taxpayer awareness, and Program SAMSAT Corner on tax compliance in the Motor Vehicle Galeria Mall. The data used in this study are primary data from the results of questionnaires. Respondents in this study Motor Vehicle Taxpayers who make tax payments in SAMSAT Corner Galeria Mall Yogyakarta. The questionnaire was distributed to 108 respondents and data that can be processed as many as 105 questionnaires. The sampling method using Accidental Sampling. Data analysis techniques in this study using multiple linear regression techniques. Results of regression analysis showed that awareness of the taxpayer and Corner Program SAMSAT positive effect on tax compliance while the Motor Vehicle Tax Payer knowledge no significant effect on motor vehicle tax compliance.Keywords: Taxpayer Knowledge, Consciousness Taxpayer, SAMSAT Corner and Compliance Program Compulsory Motor Vehicle Tax